2019
DOI: 10.1096/fj.201902298r
|View full text |Cite
|
Sign up to set email alerts
|

EPA and DHA attenuate deoxynivalenol‐induced intestinal porcine epithelial cell injury and protect barrier function integrity by inhibiting necroptosis signaling pathway

Abstract: Abbreviations: DON, deoxynivalenol; Drp1, dynamin-related protein 1; FD4, fluorescein isothiocyanate (FITC)-labeled dextran; HMGB1, high mobility group box-1 protein; IPEC-1, intestinal porcine epithelial cell line 1; LDH, lactate dehydrogenase; MLKL, mixed lineage kinase-like protein; PGAM5, phosphoglycerate mutase family 5; RIP1, receptor interacting protein kinase 1; RIPK3, receptor interacting protein kinase 3; TEER, transepithelial electrical resistance; TNFR1, tumor necrosis factor receptor 1. Abstract D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 45 publications
2
62
0
Order By: Relevance
“…In particular, intestinal cell models are widely utilized for the validation of bioactive compounds in food and feed analysis [ 15 , 26 , 27 , 28 ]. Earlier, the anti-inflammatory and anti-necroptosis activity of ω3-PUFAs were demonstrated in normal and cancer enterocyte models [ 12 , 13 , 17 ]. However, cancer cells face certain limitations as they exhibit aberrant cell surface sugars, glycoproteins, glycosylation and metabolic pathways [ 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, intestinal cell models are widely utilized for the validation of bioactive compounds in food and feed analysis [ 15 , 26 , 27 , 28 ]. Earlier, the anti-inflammatory and anti-necroptosis activity of ω3-PUFAs were demonstrated in normal and cancer enterocyte models [ 12 , 13 , 17 ]. However, cancer cells face certain limitations as they exhibit aberrant cell surface sugars, glycoproteins, glycosylation and metabolic pathways [ 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, cancer cells are not a realistic representative of normal physiology [ 14 , 15 , 16 ]. Recently, ω-3 PUFAs were shown to reverse mycotoxin damage of non-transformed IPEC-1 cells [ 17 ]. However, there has been limited research investigating the ω-3 PUFA effects on IEL injury in various stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary supplementation of n-3 PUFAs can improve the intestinal barrier function in rats. It has been reported that eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) can prevent deoxynivalenol-induced intestinal cell injury and reinforce barrier function, which is associated with the inhibition of necroptosis signaling pathway (14). Furthermore, Zhu et al found that marine oil supplementation was beneficial for the improvement of intestinal barrier function and inhibition of CRH/CRHR1 signaling pathway and mast cell density (15).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Willemsen et al [92] showed that AA, EPA, DHA and (to a lower extent) GLA enhanced basal TEER and strongly reduced IL-4-mediated permeability suggesting that those PUFAs support barrier integrity. Moreover, recent studies showed that EPA and DHA improve intestinal barrier function as indicated by higher TEER and lower FITC-dextran flux as well as increased proportions of TJ proteins located in the plasma membrane [93] (Table 2). In fact, the addition of lipase, which was used to simulate in vivo digestion and release fatty acids from the glycerol backbone, increased basal TEER in T84 cells in a dose-dependent manner.…”
Section: Effect Of Long Chain Fatty Acids On Gut Permeabilitymentioning
confidence: 98%
“…It was showed that PKC antagonists facilitate the changes mediated by GLA and DHA suggesting that PKC also may be engaged in the mechanism of leaky gut [91]. [91] Willemsen et al [92] Xiao et al [93] Onuki et al [96] Abbreviations: AA-arachidonic acid, ALA-α-linolenic acid, DHA-decosahexaenoic acid, EPA-eicosapentaenoic acid, 51 Cr-EDTA- 51 chromium-labeled ethylenediamine tetraacetic acid, GLA-γ-linolenic acid, LA-linolenic acid, NS-not significant/no change, OA-oleic acid, ↑-increased, ↓-decreased.…”
Section: Effect Of Long Chain Fatty Acids On Gut Permeabilitymentioning
confidence: 99%